From the Wharf, Port of Spain, Trinidad - (:unkn) unknown (Davidson and Todd, [Trinidad and Tobago], 2011)
The postcard shows fishing boats anchored in the Port of Spain habour also known as the St.Vincent Jetty.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fishing boats--Trinidad and Tobago; Harbors--Trinidad and Tobago; Shorelines--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Wharves--Trinidad and Tobago; Waterfronts--Trinidad and Tobago